A korai kvékerek és Magyarország egy levél és kontextusa - Maczelka Csaba (Acta historiae litterarum hungaricarum, 2011)
This paper provides an introduction to a curious case of religious contact between England and Hungary in the 17th century. After certain changes in the domestic setting, English Quakers launched a fervent (and in many cases apparently irrational) missionary campaign to foreign lands. In the New World, such efforts were rather successful. Dutch and German missions could also yield some — at least temporary — results. However, more opposition was to be encountered in contemporary Hungary, as the case of John Philly and William Moore will show. The two minor Quaker figures set out on a missionary journey to Hungary in 1662. The journey had a miserable end: the two Friends were put to prison, and they were questioned and tortured for months. Their suffering is retold in an epistle addressed to a major figure of the Dutch Quaker mission, and provides important, yet naturally biased insight into their treatment. The paper aims to provide a basic context for this letter, and to highlight some problems. for future research.